Pendekatan Filologis dalam Studi Islam - Firdian, Firdian; Indriani, Wiwik (YASIN, 2021)
Philology is one of the approaches used in the process of studying Islam and other religions. Philological approaches use texts and texts as objects of the approach they focus on, although currently the philological approach is not too trendy to do, but this approach plays a very important role in intellectual progress throughout the world because the term philology itself comes from Greek and is applied the first time by western researchers. Islamic studies is a lesson about how Islamic education is taught to students and get to know about Islamic history.